The Effect of Work Time, Workload, Work Ethos, and Work Environment on Job Satisfaction Employee at Government Agriculture Service Labuhanbatu District - Siti Rahmaida Siregar; Nova Jayanti Harahap; Abd. Halim (Quantitative Economics and Management Studies, 2023)
This research aims to analyze The Influence of Working Period, Workload, Work Ethic and Work Environment on Employee Job Satisfaction at the Agriculture Office of the Government of Labuhanbatu Regency. The research method used in this research is quantitative. In this study, the population were employees of the Labuhanbatu Regency Government Agriculture Service as many as 42 people. The research sample usessaturated sampling technique by attracting the entire existing population to be used as a research sample witha total of 42 people. Data collection techniques used were observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The results of the research prove that the Working Periodpositive and significant effect onEmployee Job Satisfaction at the Agriculture Office of the Labuhanbatu Regency Government. Workloadpositive and significant effect onEmployee Job Satisfaction at the Agriculture Office of the Labuhanbatu Regency Government. Work ethicpositive and significant effect onEmployee Job Satisfaction at the Agriculture Office of the Labuhanbatu Regency Government. Work environmentpositive and significant effect onEmployee Job Satisfaction at the Agriculture Office of the Labuhanbatu Regency Government. Tenure, Workload, Work Ethic and Work Environmentsimultaneously positive and significant effect onEmployee Job Satisfaction at the Agriculture Office of the Labuhanbatu Regency Government. The coefficient of determination is 0.824, meaning that employee job satisfaction can be explained by variablesWorking Period (X1), Workload (X2), Work Ethic (X3) and Work Environment (X4)of 82.4%, while the remaining 17.6% can be explained by other variables not examined in this study.